Interferometric diagnostics for magnetic spots detection. Issue 69 (10th September 2015) - Ligi, R.
Abstract : The signature of activity in general, and of stellar magnetic spots in particular, is present in every measurements, including interferometric ones. Indeed, stellar spots can be found on many stellar surfaces, their size and number varying according to their host's magnetic field and rotational velocity. To correctly determine stellar parameters, it is thus necessary to determine and extract stellar activity's signals. Interferometric observables are disturbed by activity, and this observing technique thus constitutes a good way of probing stellar surface. However, magnetic spots sometimes mimic other phenomenon, like a transiting exoplanet. In that case, the combination of several observing techniques, like photometry and interferometry, is mandatory to extract the planetary signal from the spot's one, and then characterize the exoplanet.